An In Silico Approach for Identification of P20 Candidate using Bioinformatics Tool (Asian Journal of Pharmaceutics (AJP), 2023)
Background: Parthenium hysterophorus is a species of flowering plant in the family Asteraceae, locally knownas carrot grass, congress grass, or Gajar Ghas. Objective: The study was aimed to investigate which orthologuesof P. hysterophorus genes that might encode the P20 protein. Methods: Low-abundance proteins were found afterfractionating P. hysterophorus leaf proteins in polyethylene glycol. Samples treated at −80°C shortened the timeneeded for protein to precipitate to 2 h. In addition, sonication was employed to remove non-protein impurities,which elevated protein solubility and enhanced MALDI-TOF mass spectrometry for protein identification.Results: Tryptic digest of purified protein revealed that the predicted size of the protein is ~20kDa by MALDI-TOFand identification of peptides present in the P20 protein by peptide sequence analysis. Conclusion: This studydescribes how a combination of bioinformatics and proteomics approaches led to the identification of novel P20candidates.